Modernity is incompatible with planetary limits: Developing a PLAN for the future. (November 2021) - Murphy, T.W.; Murphy, D.J.; Love, T.F.; LeHew, M.L.A.; McCall, B.J.
Abstract: This age of modernity is characterized by consistent growth in energy use, economic activity, and resource consumption, and a generally increasing standard of living—albeit inequitably distributed. All currently living humans, and most academic disciplines, have developed in this age, which appears normal and indefinite to us. But modernity has been enabled by the rapid and accelerating expenditure of our one-time inheritance of fossil fuels, and by drawing down the resources and ecosystems of our finite Earth—none of which can be sustained as we transition from a resource-rich frontier to a human-dominated planet. Climate change is often singled out as modernity's existential crisis, but it is only one of a series of interlocking challenges constituting an unprecedented predicament that must be understood and mitigated in order to live within planetary limits. While energetic and technological challenges attract significant attention, arguably the greatest challenges are conceptual or even cultural. In particular, as we review in this Perspective, today's political economy has been designed to value short-term financial wealth over the real treasure of Earth's functioning ecosystems, to discount the future at the expense of the present, and to demand infinite exponential growth…which is simply impossible on a finite planet. Given all this, humanity should view its present overshoot-prone trajectory with tremendous suspicion, humility, and concern. We call for the establishment of a transdisciplinary network of scholars from across the entire academic landscape to develop a global understanding of planetary limits and how humanity can adapt to the associated realities. We present a set of foundational principles to serve as a starting point to anchor this network and drive a new area of focused inquiry to develop a shared vision of viable future paths.